2015
DOI: 10.1007/s00423-015-1341-8
|View full text |Cite
|
Sign up to set email alerts
|

Algorithm for early discharge after total thyroidectomy using PTH to predict hypocalcemia: prospective study

Abstract: PTH determination at 3 h postoperatively is a reliable predictor of hypocalcemia. According to the proposed algorithm, patients with less than 80% drop in PTH levels can be safely discharged the day of the surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 21 publications
3
23
2
Order By: Relevance
“…Based on the analysis of published Australian data, [21][22][23] The Australian Endocrine Surgeons Guidelines currently recommends the routine measurement of PTH 4 hours after total thyroidectomy to guide postoperative calcium supplementation. 24 Schlottman et al 25 suggested that the greatest sensitivity and specificity in predicting hypocalcemia are achieved when looking at the decline in PTH from baseline rather than the absolute value, demonstrating that no patient with a decrease in PTH <35% developed hypocalcemia and all patients with a decrease >80% (14% of the cohort) became hypocalcemic in a study of 106 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the analysis of published Australian data, [21][22][23] The Australian Endocrine Surgeons Guidelines currently recommends the routine measurement of PTH 4 hours after total thyroidectomy to guide postoperative calcium supplementation. 24 Schlottman et al 25 suggested that the greatest sensitivity and specificity in predicting hypocalcemia are achieved when looking at the decline in PTH from baseline rather than the absolute value, demonstrating that no patient with a decrease in PTH <35% developed hypocalcemia and all patients with a decrease >80% (14% of the cohort) became hypocalcemic in a study of 106 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Inferior laryngeal nerves palsy also generally arises early, in about 87% of cases, with the appearance of dysphonia within the first 24 hours after surgery, but later onsets are also described, up to 14 days after surgery, in the remaining 13% of cases (53)(54)(55)(56)(57). Conversely postoperative hypocalcemia may also occur after 48-72 hours after surgery, and is the most common cause of prolonged hospitalization after thyroid surgery (15,58). Transient hypocalcemia may occur in 25% of patients undergoing bilateral thyroid surgery and is permanent in 0.9-14% of cases (59,60).…”
Section: Discussionmentioning
confidence: 99%
“…The causes that are opposed to early discharge are possible bleeding complications, inferior laryngeal nerves palsy and hypocalcemia (11)(12)(13)(14), but unlike the first two which are generally well detectable within the first 24 hours after surgery, the latest one is called into question, as often detectable beyond 24-48 hours after surgery (6,(15)(16)(17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Hypoparathyroidism may be asymptomatic and self-limiting but can also lead to hypocalcaemia with symptoms of paraesthesia and muscle spasms manifesting within the first 24 h after surgery [14]. The incidence of complication varying from 1 to 50% [3, 10, 14-16] is in part related to the variety of methods used to define the condition.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common complications following total thyroidectomy is hypoparathyroidism [1-14] caused by devascularization or accidental resection of one or more of the parathyroid glands [15]. Hypoparathyroidism may be asymptomatic and self-limiting but can also lead to hypocalcaemia with symptoms of paraesthesia and muscle spasms manifesting within the first 24 h after surgery [14].…”
Section: Introductionmentioning
confidence: 99%